Models of Radio Waves Scattering by Bedding Surfaces and Their Using in Radar Remote Sensing Systems - Kalmykov, A. I.; Fuks, I. M. (Видавничий дім «Академперіодика», 2012)
Models of Radio Waves Scattering by Bedding Surfaces and Their Using in Radar Remote Sensing Systems